Post-operative mortality, missed care and nurse staffing in nine countries: A cross-sectional study - Ball, Jane E.; Bruyneel, Luk; Aiken, Linda H.; Sermeus, Walter; Sloane, Douglas M.; Rafferty, Anne Marie; Lindqvist, Rikard; Tishelman, Carol; Griffiths, Peter (International journal of nursing studies, 2018)
Variation in post-operative mortality rates has been associated with differences in registered nurse staffing levels. When nurse staffing levels are lower there is also a higher incidence of necessary but missed nursing care. Missed nursing care may be a significant predictor of patient mortality following surgery. Examine if missed nursing care mediates the observed association between nurse staffing levels and mortality. Data from the RN4CAST study (2009–2011) combined routinely collected data on 422,730 surgical patients from 300 general acute hospitals in 9 countries, with survey data from 26,516 registered nurses, to examine associations between nurses’ staffing, missed care and 30-day in-patient mortality. Staffing and missed care measures were derived from the nurse survey. A generalized estimation approach was used to examine the relationship between first staffing, and then missed care, on mortality. Bayesian methods were used to test for mediation. Nurse staffing and missed nursing care were significantly associated with 30-day case-mix adjusted mortality. An increase in a nurse’s workload by one patient and a 10% increase in the percent of missed nursing care were associated with a 7% (OR 1.068, 95% CI 1.031–1.106) and 16% (OR 1.159 95% CI 1.039–1.294) increase in the odds of a patient dying within 30days of admission respectively. Mediation analysis shows an association between nurse staffing and missed care and a subsequent association between missed care and mortality. Missed nursing care, which is highly related to nurse staffing, is associated with increased odds of patients dying in hospital following common surgical procedures. The analyses support the hypothesis that missed nursing care mediates the relationship between registered nurse staffing and risk of patient mortality. Measuring missed care may provide an ‘early warning’ indicator of higher risk for poor patient outcomes.